Floral morphology and anatomy of Ophiocaryon, a paedomorphic genus of Sabiaceae - Thaowetsuwan, P. (2017)
Background and Aims Ophiocaryon is a lesser known genus in Sabiaceae. This study examines flowers of six Ophiocaryon species in comparison with Meliosma alba, to identify taxonomically informative characters for understanding relationships within the family Sabiaceae, to imply previously unknown pollination mechanisms of Ophiocaryon, and to contribute to the placement of Sabiaceae within the early-diverging eudicots. • Methods Floral morphology and anatomy of six Ophiocaryon species and M. alba were studied and described using scanning electron microscopy, clearing techniques and resin sectioning. • Key Results Novel characters of Ophiocaryon were identified, e.g. conical cells on petals, different kinds of orbicules in anthers, stomata on nectary appendage tips and ovary, two distinct surface patterns on stamens and ovary, tanniferous cell layers in the ovary wall, and acorn-shaped unitegmic ovules with very short integuments. Comparison of floral characters between Ophiocaryon and Meliosma found that the calyx, corolla, androecium and gynoecium of Ophiocaryon resemble an undeveloped state of the latter taxon, reflecting a paedomorphic regression of the flower of Ophiocaryon. The flower morphology and anatomy of Ophiocaryon was compared with its putative sister species M. alba, but no clear shared derived characters could be detected. Moreover, the findings of scent, presence of conical cells on petals and a nectary suggest flowers are pollinated by small insects with a secondary pollen presentation on the cupula of fertile stamens. • Conclusions We found that Ophiocaryon may be derived from ancestors that were similar to extant Meliosma in their flower structure and pollination mechanism. However, the lack of shared derived characters between Ophiocaryon and its phylogenetic sister group M. alba is puzzling and requires further investigations on the diversity of the latter species. ©The Author 2017. Published by Oxford University Press on behalf of the Annals of Botany Company.